Manual do Estudante de Latim (1855), de Joaquim da Silva : orientações e práticas pedagógicas para o ensino latinista na Paraíba - Lima, Karla D'angela de (2024)
This dissertation, part of the History of Education track within the Graduate Program in Education (PPGE) at the Federal University of Paraíba (UFPB), has the following specific objectives: i) To understand the teaching of Latin in the history of Brazil and Paraíba; ii) To identify the production and circulation process of the book "Manual do Estudante de Latim"; iii) To identify and analyze the educational guidelines and pedagogical practices in Joaquim da Silva's "Manual do Estudante de Latim". To achieve these goals, this research adopts a Cultural History approach, drawing on references such as Chartier (1998a) and other relevant authors — Cardoso (2011), Saviani (2013), Amarante (2018), Franca (1952), Mello (1956), Sena (2017), and Pinheiro (2002) — who assisted in analyzing various documentary sources, including letters, newspapers, reports, biographies, and laws. These sources reveal the role of Latin teaching throughout history as a tool for educational formation. In analyzing the "Manual do Estudante de Latim," we found that the work offered much more than Latin grammar lessons. It deconstructed Latin Classics to present the context and elements that contributed to the creation of these texts, showcasing the historical and social constitution of Antiquity that influenced their production and is still used in part of Latin teaching and learning. With the book in hand and supported by the aforementioned sources, we examined the organization and pedagogical practices that guided Latin teaching in the 19th century. This highlighted the transition of Latin from one of the most important subjects of the period to one of the least significant. This process also revealed significant changes in the educational landscape, as the teaching of classical languages was gradually replaced by the teaching of modern languages, indicating a paradigm shift from a more humanistic to a more modern approach. Based on these arguments, we believe that this study contributes to the understanding of the content and circulation of this cultural object for the organization of Latin teaching in the History of Education in Paraíba.